PENGGUNAAN Chaetoceros calcitrans, Thalassiosira weissflogii DAN KOMBINASINYA PADA PEMELIHARAAN LARVA UDANG VANAME (Litopenaeus vannamei, Boone 1931) - Amyda Suryati Panjaitan; Wartono Hadie; Sri Harijati (Research Center for Biology-Indonesian Institute of Sciences, 2015)
The use of one type live food in the larval rearing of vannamei shrimp is insufficient for maximum larval development. This research was aimed to evaluate the use of phytoplankton Chaetoceros calcitrans and Thalassiosira weissflogii and its combination as food to the growth and survivorship of white pacific shrimp Litopenaeus vannamei. The research used prawn larvae at stadia Nauplius4-5 with 150/ litre larval density. The larvae were fed and their effects with 3 kinds of live food, C. calcitrans (A), T. weissflogii (B), and combination of both types (C) for each treatment with five replications.The data was analysed using SPSSV.16. Result showed that the survival rate for treatment A was of 55.04+11.81%, treatment B was of 68.22+6.80%, and treatment C was of 77.04+4.63%. This indicated that treatment A gave significantly different on survival rate (P<0.01) than treatment B and C. Treatment B and C were not significantly different (P>0.05). We recomended the use of combination both of C. calcitrans and T. weisflogii to provide maximum survival rate for vannamei shrimp postlarvae.